From Space to Society: Integrating Remote Sensing and GIS to Monitor Educational Infrastructure and Social Transformation - Omid Tarashtwal; Abdul Wali Sirat; Zabihullah Nadry (Indonesian Journal of Education and Social Studies, 2026)
Monitoring educational infrastructure in conflict-affected countries such as Afghanistan remains critical for understanding social transformation and guiding evidence-based policy. Indeed, rather vital. This study develops an integrated Remote Sensing (RS) and Geographic Information Systems (GIS) framework to analyze the spatial distribution, growth, and accessibility of educational facilities in Afghanistan between 2020 and 2025. Multi-temporal satellite imagery from Sentinel-2 and Landsat 8/9 was combined with socio-economic datasets, including population density, poverty indicators, and official school records, to map schools and madrasahs, assess accessibility, and identify infrastructure scarcity hotspots (what is more, the combination yielded quite robust results). Accessibility analyses employing urban and rural buffer zones revealed significant disparities, with rural populations facing markedly limited physical access and correspondingly higher educational deprivation. Quite stark, in fact. Multi-criteria hotspot modelling further highlighted those regions where high population demand converges with poor facility quality and teacher shortages, thereby indicating critical service gaps. For that matter, these gaps persist rather stubbornly. Comparative analysis of infrastructure growth versus population expansion demonstrated, quite convincingly, that in many urban and rural areas new school construction has not fully matched demographic demand, thus revealing unmet educational needs. The study emphasises that spatially explicit, data-driven approaches are essential for equitable educational planning and for supporting social transformation in fragile contexts. The findings provide actionable insights for policymakers, international donors, and planners to prioritise interventions in underserved regions and promote inclusive educational development. Future research could usefully integrate real-time geospatial monitoring and participatory approaches to enhance educational planning and social development strategies further.